Assessment of Student Satisfaction with E-learning in Jordan Using TAM and UTAUT as a Mediator for Synchronous and Asynchronous Learning - Aldiabat, Khaled; Gharaibeh, Malik; AlQudah, Nidal (Society of Visual Informatics, 2024)
This study aims to evaluate student satisfaction with e-learning in Jordan by combining the Technology Acceptance Model (TAM) and the Unified Theory of Acceptance and Use of Technology (UTAUT). This research also delved into the study of the mediating role played by both synchronous and asynchronous learning and their impact on students’ satisfaction with e-learning. Data was collected through a questionnaire distributed to 590 students studying at four private Jordanian universities in northern Jordan. To analyse the study model, Smart PLS was used because it offers a robust methodology for such complex constructs. The results show that both synchronous and asynchronous learning significantly and positively affect students’ satisfaction with e-learning. The results also revealed that the relationship between synchronous learning and perceived usefulness was statistically significant. Regarding asynchronous learning, the relationship with perceived ease of use was positive and statistically significant. Turning to the TAM and UTAUT variables as independent variables, the results revealed a direct and statistically significant relationship between these variables and students’ satisfaction with e-learning. This study provides valuable insights into the factors that influence student satisfaction with e-learning in Jordan and presents a new approach by integrating synchronous and asynchronous learning as a mediator within the TAM and UTAUT frameworks. The findings highlight the nuances of technology acceptance and use in the context of e-learning, which can benefit educational institutions and policymakers in enhancing the e-learning experience for students in Jordan.